Neopersectania un nuevo genero de noctuido hadenino (Lepidoptera: Noctuidae: Hadeninae) - Rodriguez, M.A.=700 1 Angulo, A.O.
(En, Es)
ilus., 15 ref.
Keywords: LEPIDOPTERA; NOCTUIDAE; ANATOMIA ANIMAL; CHILE; SCRIPTANIA; PERSECTANIA